Effects of Salts on Structural, Physicochemical and Rheological Properties of Low-Methoxyl Pectin/Sodium Caseinate Complex - Shengyu Fan; Fang Fang; Ailing Lei; Jiong Zheng; Fusheng Zhang (Foods, 2021)
The addition of salts is an effective way to improve the properties of polysaccharide/protein complexes for use in foods. However, there is no comparative study on the effects of different ions on the complex system of low methoxyl pectin (LMP)/ sodium caseinate (CAS) complex. The effects of different concentrations of three salt ions (Na+, K+, Ca2+) on the physicochemical and rheological properties of the LMP/CAS complex were determined in this study, and the structure of LMP/CAS complex was characterized. The results showed that the addition of these three salt ions affected zeta potential, particle size, and turbidity of the LMP/CAS complex, and lead the LMP/CAS complex to form a more regular and uniform network structure, which helped improve its stability, solubility, and rheological properties. The particle size and turbidity value of the complex achieved with Ca2+ were higher than those obtained using Na+ and K+. Moreover, the secondary structure of the proteins in the complex changed to adding high concentrations of Ca2+. Our study provides valuable information for the application of the LMP/CAS complex in the food industry.